Evil and the many universes response - Megill, Jason (International journal for philosophy of religion, 2011)
I formulate and defend a version of the many universes (or multiverse) reply to the atheistic argument from evil. Specifically, I argue that (i) if we know that any argument from evil (be it a logical or evidential argument) is sound, then we know that God would be (or at least probably would be) unjustified in actualizing our universe. I then argue that (ii) there might be a multiverse and (iii) if so, then we do not know that God would be (or at least probably would be) unjustified in actualizing our universe. It follows that we cannot know that the atheistic argument from evil is sound, in which case we cannot be certain that the argument succeeds, and so it is rational to refuse to reject theism because of such arguments.